2004
DOI: 10.1261/rna.5229704
|View full text |Cite
|
Sign up to set email alerts
|

A single polypyrimidine tract binding protein (PTB) binding site mediates splicing inhibition at mouse IgM exons M1 and M2

Abstract: Splicing of mouse immunoglobulin (IgM) exons M1 and M2 is directed by two juxtaposed regulatory elements, an enhancer and an inhibitor, located within the M2 exon. A primary function of the enhancer is to counteract the inhibitor, allowing splicing to occur. Here we show that the inhibitor contains two binding sites for polypyrimidine tract binding protein (PTB). Mutational analysis indicates that only one of these sites is necessary and sufficient to direct splicing inhibition both in vitro and in vivo. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 35 publications
1
58
1
Order By: Relevance
“…This complex is not splicing-specific, as it assembles not only on T7 pre-mRNAs but also on T7 RNAs lacking functional splice sites (Konarska and Sharp 1986;Michaud and Reed 1991;Bennett et al 1992). It is well known that at least some hnRNP proteins inhibit splicing and that these proteins compete with essential splicing factors for binding to pre-mRNA in vitro (Caputi et al 1999;Wagner and Garcia-Blanco 2001;Zhu et al 2001;Black 2003;Rooke et al 2003;Fu 2004;Shen et al 2004;Wang et al 2004;Han et al 2005;Rothrock et al 2005). Consistent with this conclusion, previous studies indicate that the H complex is not a functional precursor to the spliceosome (Michaud andReed 1991, 1993).…”
Section: Discussionmentioning
confidence: 62%
“…This complex is not splicing-specific, as it assembles not only on T7 pre-mRNAs but also on T7 RNAs lacking functional splice sites (Konarska and Sharp 1986;Michaud and Reed 1991;Bennett et al 1992). It is well known that at least some hnRNP proteins inhibit splicing and that these proteins compete with essential splicing factors for binding to pre-mRNA in vitro (Caputi et al 1999;Wagner and Garcia-Blanco 2001;Zhu et al 2001;Black 2003;Rooke et al 2003;Fu 2004;Shen et al 2004;Wang et al 2004;Han et al 2005;Rothrock et al 2005). Consistent with this conclusion, previous studies indicate that the H complex is not a functional precursor to the spliceosome (Michaud andReed 1991, 1993).…”
Section: Discussionmentioning
confidence: 62%
“…Structurally, PTB consists of four RNA recognition motif (RRM) domains, and its optimal binding site determined by SELEX comprises motifs such as UCUU in a generally pyrimidine-rich context (Perez et al 1997a). Motifs identical or similar to this have been found to act as splicing silencer elements in a wide range of pre-mRNA substrates and are often located adjacent to exons that are included with neuronal or muscle specificity (Mulligan et al 1992;Ashiya and Grabowski 1997;Chan and Black 1997;Perez et al 1997a;Gooding et al 1998;Southby et al 1999;Zhang et al 1999;Wagner and Garcia-Blanco 2002;Shen et al 2004;Izquierdo et al 2005;Sauliere et al 2006). Structurefunction analysis initially indicated that RRMs 3 and 4 are principally responsible for RNA binding, while the N-terminal half of the protein might be responsible for PTB dimerization (Perez et al 1997b;Oh et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies failed to find increased ESE-dependent U2AF cross-linking (Guth et al 1999;Kan and Green 1999;Li and Blencowe 1999), possibly due to different experimental conditions (Guth et al 2001). In one instance, an ESE promoted splicing by counteracting the negative effect of a downstream splicing silencer (Kan and Green 1999;Shen et al 2004a). Another alternative to the SR/U2AF protein-protein interaction model for ESE-mediated splicing activation is based on a recent report that a tethered RS domain specifically contacts the branchpoint (Shen et al 2004b).…”
mentioning
confidence: 99%